Diversity in Psychological Research Activities: Quantitative Approach With Topic Modeling - Otsuka, Sachio; Ueda, Yoshiyuki; Saiki, Jun (Frontiers in Psychology, 2021)
Recent cultural studies have discussed universality and diversity in human behavior using numerous samples investigated worldwide. We aimed to quantitatively extend this discussion to various research activities in psychology in terms of geographic regions and time trends. Most psychology departments have specialists in various fields of psychology. Further, research institutions in all regions typically aim to provide systematic and balanced research education. Nevertheless, most researchers recognize universal features and patterns of diversity in research activities in psychology in terms of regional differences and time trends. However, these arguments remain intuitive and vague, and no studies have conducted quantitative analyses. To this end, we conducted topic modeling for manuscript abstracts of psychological articles, taking the regions of authors affiliations and publication periods as covariates. The results showed that the topic proportions related to basic research were high in North-Central America, whereas those related to clinical research were high in Europe. Interestingly, the regional differences shown by topic modeling were not observed in the frequency analysis of keywords, indicating that topic modeling revealed implicit characteristics. Moreover, we observed an increasing trend of neuroscience topics across publication periods. However, this trend was not true for the psychology journal, Psychological Science. Taken together, our results suggest diversity of geographic regions and time periods in research activities in psychology. More importantly, our findings indicate that not only does universality not hold for human behavior, it also does not hold for research activities on human mental processes.